Structural behaviour of thin-walled composited-filled beams / Fauzi, M.A. and Ghazali, E. - Fauzi, M.A.; Ghazali, E. (2014)
This paper presents a laboratory study to determine load and displacement relationship of the beams subjected 4-point loading, load and strain relationship of the beams, failure mode of the beams and to compare the experimental results and theoretical calculations. In this study, the number of specimens to be tested is 4. Field study would involve the experiment of the thin-walled composite-filled beams. The strength and failure modes of the beams are found to depend on the interface connections. The specimens were water cured for 7 days after removing them from the mould. Compressive and tensile strength tests were carried out on the specimens. Analytical models for the design of beams are developed and their performance is validated through experimental results using partial connection. The theoretical yield stress is 2667μm/m and these showed that the steel have yielded at ultimate loads. The ratio of experimental to theoretical values (derived from appropriate degree of restraint) ranges from 0.80 to 0.91, this shows reasonable agreement.